New Results in an Old Framework: Comment on Samuelson and Modigliani - Robinson, Joan (Review of Economic Studies, 1966)
Journal Article Comment on Samuelson and Modigliani Get access Joan Robinson Joan Robinson Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 4, October 1966, Pages 307–308, https://doi.org/10.2307/2974427 Published: 01 October 1966